Value of abdominal pressure by using abdominal belt in facilitating colonoscopic procedure in Egyptian patients - Aya Mohamed Mahros; Eslam Mohamed El Shenawy; MohammedHussien Ahmed (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the role of applying abdominal pressure using abdominal belt in overall improvement in the practice of colonoscopy. Method: The randomised, single-blind case-control study was conducted from March 2020 to March 2021 at Kafrelsheikh University Hospital, Cairo, Egypt, and comprised patients of either gender aged 30-70 years who underwent elective colonoscopy. The patients were randomised into belly belt group A and control group B. The endoscopist was blinded to the group assignment. Time needed to reach the caecum, requirement for changing the position, dosage of anaesthetic agents, completion of endoscopy, ileal intubation, post-procedure pain and abdominal distension were noted and compared between the groups. Data was analysed using SPSS 24. Result: Of the 160 patients, 80(50%) were in each of the two groups. There were 38 (47.5%) males and 43 (52.5%) (females) in group A with mean age 55.8±4.1 years. In group B, there were 40(50%) males and as many females with mean age 55.4±3.4 years. Group A had significantly better overall outcomes than group B (p<0.05) except procedure complications (p=0.526). Conclusion: Abdominal belt was found to be an effective and simple method to improve the practice of colonoscopy. Keywords: Colonoscopy, Ileum, Cecum, Colorectal neoplasms, Intubation, Intratracheal, Anaesthesia.